Penerapan Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode HIRARC Pada UMKM Pabrik Tahu - Valentina Monoarfa; Ridwan Nur Bahri Miolo (Mopolayio : Jurnal Pengabdian Ekonomi, 2022)
This study discusses the application of Occupational Safety and Health (K3) in the activity of the tofu-making process at the Mokar Jaya tofu factory. The purpose of this research is to identify occupational safety and health (K3) hazards, to know risk of potential hazards and risk control for factory workers using the HIRARC (Hazard Identification Risk Assessment and Risk Control) method. The results of the risk assessment of 14 hazards from 10 processes of tofu production activities classified as low risk 57%, medium 36%, high 43%, extreme 0%. Low risk is a priority for self-control from the highest risk because there are no risks with extreme categories. The results of risk control are recommended for each activity to wear PPE (Personal Protective Equipment) and change body position so that there is no ergonomic risk.